Partisipasi Masyarakat Dalam Pembangunan Desa di Desa T’eba dan Desa T’eba Timur Kecamatan Biboki Tanpah, Kabupaten Timor Tengah Utara - Yoseph Nainahas; Saryono Yohanes; Rafael Rape Tupen (Demokrasi: Jurnal Riset Ilmu Hukum, Sosial dan Politik, 2025)
This study aims to analyze community participation in village development in T’eba Village and T’eba Timur Village, Biboki Tanpah Subdistrict, Timor Tengah Utara Regency, and to identify the factors that hinder it. Village development is one of the key elements in improving community welfare. However, low community participation poses a challenge that hampers the achievement of inclusive and sustainable development goals. T’eba Village exhibits a higher level of community participation compared to T’eba Timur Village, yet both face challenges that affect the success of their development. The research methodology employed is empirical juridical with socio-legal and conceptual approaches. Primary data were obtained through interviews, observations, and questionnaires, while secondary data were sourced from official documents and related literature. Data analysis was conducted using qualitative descriptive techniques to interpret the research findings. The results show that community participation in T’eba Village reached 82.61%, whereas in T’eba Timur Village, it was only 30.44%. This disparity is attributed to higher community awareness in T’eba Village and better support from the village government in engaging the community. Factors hindering community participation include educational disparities, a lack of awareness about the importance of village development, economic conditions prioritizing subsistence needs, and community perceptions of the effectiveness of the village government. For example, residents of T’eba Timur Village are less involved because they feel that development programs do not directly benefit their livelihoods, particularly in agriculture, which is their primary occupation. This study recommends enhancing community involvement through education, economic empowerment, and strengthening the capacity of village governments to create inclusive and transparent participatory mechanisms. Moreover, it emphasizes the need for coordination between the community and village governments to formulate development policies that are more responsive to local needs. With this approach, village development can become more relevant, sustainable, and impactful for the community.